Thyroid Cancer Screening Using Tumor-Associated DN T Cells as Immunogenomic Markers - Imam, Shahnawaz; Paparodis, Rodis D.; Rafiqi, Shafiya Imtiaz; Ali, Sophia; Niaz, Azra; Kanzy, Abed; Tovar, Yara E.; Madkhali, Mohammed A.; Elsherif, Ahmed; Khogeer, Feras; Zahid, Zeeshan A.; Sarwar, Haider; et al. (Frontiers in Oncology, 2022)
Background: Thyroid nodules are an extremely common entity and surgery is considered the ultimate diagnostic strategy in those of unclear malignant potential. Unfortunately, strategies aiming to predict the risk of malignancy have inadequate specificity. Our group recently found that the microenvironment of thyroid cancer is characterized by an enhanced immune invasion and activated immune response, mediated by double negative T-lymphocytes (CD3+CD4-CD8-) (DN T), which are believed to enable or promote tumorigenesis. In the present work, we try to use the DN T cells’ proportion in thyroid fine needle aspiration (FNA) material, as a predictor of the risk of malignancy. Methods: We recruited 127 patients and obtained ultrasound guided FNA samples from subjects with cytology positive or suspicious for malignancy and from those with benign nodular goiter some associated with compressive symptoms (such as dysphagia, shortness of breath, or hoarseness), Hashimoto thyroiditis and Graves’ disease. Out of 127, we investigated 46 FNA samples of patients who underwent total thyroidectomy and for which post-operative histological diagnosis by the academic pathologists was available. We specifically measured the number of cells expressing (CD3+CD4-CD8-) (Double negative T-lymphocytes: DN T) as a function of total CD3+ cells in FNA samples using flow cytometry. We correlated their FNA DN T cell proportions with the pathological findings. Results: The DN T cells were significantly more abundant in lymphocytic infiltrates of thyroid cancer cases, compared to benign nodule controls (p <0.0001). When the DN T cell population exceeded a threshold of 9.14%, of total CD3+ cells, the negative likelihood ratio of being cancer free was 0.034 (96.6% sensitivity, 95% CI, 0.915 to 1.000, p <0.0001). DN T cells at <9.14% were not found in any subject with benign disease (specificity 100%). The high specificity of the test is promising since it abolishes false positive diagnosis and in turn unnecessary surgical procedures. Conclusion: The present study proposes DN T cells’ proportion as a pre-operative diagnostic signature for thyroid cancer which with integration of RNA transcriptomics can provide a simplified technology based on PCR assay for the ease of operation.